Analisis Perbandingan Sifat Fisika dan Mekanika Papan Laminasi Kayu Jati Putih (Gmelina arborea. Roxb) dan Papan Lamninasi Bambu Petung (Dendrocalamus asper): Comparison Analysis of Physical and Mechanical Properties of White Teak Wood (Gmelina arborea. Roxb) Laminate Board and Petung Bamboo (Dendrocalamus asper) Lamniation Board - Febriana Tri Wulandari; I Gde Dharma Atmaja (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
This study of laminated boards wants to compare laminated boards made of wood and non-wood raw materials. For wood, use white teak (Gmelina arborea. Roxb) and non-wood using petung bamboo (Dendrocalamus asper). Teak wood is easy to work either by machine or by hand. It has an average fiber length of 1.32 mm with a diameter of 24.8 μm. Teak wood is included in durable class 1 and strong class II, has a fairly good nail resistance and can withstand rust with the age of an old tree. Petung bamboo has a diameter that can reach 20 cm with a wall thickness of 1-3 cm, making it suitable for use as laminated bamboo. To see the difference in strength of the two boards, it is necessary to test the physical and mechanical properties. The purpose of this study is to compare the strength of the physical and mechanical properties of laminated boards made of wood and non-wood so that they can provide recommendations according to their use. The test values for physical and mechanical properties of white teak laminated boards and petung bamboo laminated boards showed no significant difference. All tests of physical and mechanical properties have met the standard except for the thickness shrinkage test for white teak laminated boards which did not meet the standards. Based on the value of testing the physical and mechanical properties, the laminated boards of white teak and petung bamboo are included in the strong class III which can be used for indoor construction materials.